Chloroquine: An Old to be Repurposed Drug For COVID-19 Infection (Risk and Benefit) - Putra, Oki Nugraha; Faizah, Ana Khusnul; Nurrahman, Nani Wijayanti Dyah; Hardiyono, Hardiyono (Pharmaceutical Sciences and Research, 2020)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) causes Coronavirus Disease 2019 (COVID-19) with a high rate of mortality. Chloroquine and hydroxychloroquine have been used for antimalarial and autoimmune diseases for many years. Due to low toxicity and well tolerability as well as immunomodulatory properties, these drugs are proposed to treat viral infection. Some studies, both in vitro and in a clinical setting, have been evaluated for their ability to treat SARS- CoV-2 as promising therapies. Although The National Agency of Drugs and Food Control of The Republic of Indonesia issued emergency authorization for chloroquine and hydroxychloroquine to be used against COVID-19 infection, the efficacy of these drugs is still based on small clinical non- randomized trials with a limited number of patients. However, the use of these drugs without any risks. The safety of these drugs to be used in COVID-19 patients is lacking. Some experts noticed that the drugs cause harmful adverse effects, especially a harmful QT prolongation. In Indonesia, until now, no study evaluates the effectiveness as well as the safety of these drugs to be used in COVID-19 infection. This article will discuss the role of chloroquine or hydroxychloroquine and its safety to be used against COVID-19 infection.